Infectious Diseases Society of America Guidelines on the Diagnosis of COVID-19: Serologic Testing - Mary K. Hayden; Ibrahim K El Mikati; Kimberly E. Hanson; Janet A. Englund; Romney M. Humphries; Francesca Lee; Mark Loeb; Daniel J. Morgan; Robin Patel; Omar Al Ta’ani; Jamil Nazzal; Shahad Iqneibi; et al. (2024)
The role of serologic testing for SARS-CoV-2 has evolved during the pandemic as seroprevalence in global populations has increased. The Infectious Diseases Society of America (IDSA) convened an expert panel to perform a systematic review of the coronavirus disease 2019 (COVID-19) serology literature and construct updated best practice guidance related to SARS-CoV-2 serologic testing. This guideline is an update to the fourth in a series of rapid, frequently updated COVID-19 guidelines developed by IDSA.